Mustahiq: Studi Kasus Penerima Zakat Pada Masyarakat Skouw Sae Distrik Muara Tami Kota Jayapura - Kelibia, Muhidin; Muhandy, Rachmad Surya; Amirullah, Amirullah; Muhyiddin, Syaiful (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
This study aims to determine the model of zakat distribution which is carried out by the community and to find out the lack of understanding of the groups who are entitled to receive zakat. This study also aims to find out the institutions that applied in society as well as how the perspective of Islamic law regarding the distribution of zakat in Skouw Sae Village, Muara Tami District, Jayapura City. It is qualitative research, using the paradigm of social phenomenology. Research results: There are quite a lot of Muzaqih included in the category of poor and converts. The formation of Amil by the administrators of the Al-Aqsa Skouw Sae mosque is carried out every year before the holy month of Ramadan. In addition, not all Muslims who are appointed to be Amil knows the terms and duties of it, so that the lack of public knowledge about Islam causes an inability to understand the assets that must be zakated which results in public ignorance about the 8 Asnabs that are obliged to receive zakat. The lack of religious guidance carried out in the community causes knowledge of the obligation to pay zakat to be known to the public, but not in detail about what assets are required to be tithe, the nisab, and who is obliged to receive zakat. This knowledge is only owned by the Imam of the Mosque. The point of view of Islamic law regarding zakat in Skouw Sae that paying zakat is a must that should be done by every Muslim which is not included in the 8 asnabs, its implementation is regulated in the Qur'an and Hadith. Social institutions: Lack of Dai/Mubaliq who can provide continuous religious guidance. Economic Institutions: Economic factors support a person to make the habit of issuing zakat. Cultural Institutions: Habits carried out by people who have the ability not to pay zakat on their wealth to others lead to imitations that are carried out to the next generation, thus creating a new culture in the community.